The information base for the planning of the diversified educational field. IIEP Research Report No. 68 - Carr-Hill, Roy A (IIEP, 2020)
Draws lessons from several efforts made at national, regional and international levels to develop a data base on non-formal education; reviews the approaches and methodologies used and assesses the main findings; discusses the relevance of such a data base for educational planning and management as well as the feasibility of doing further research in this field.